La mia scoperta dell’America: la mia scoperta dell’America La prima esperienza americana di un giovane ricercatore (Chimica nella Scuola, 2022)
The author tells his first American life experience as a researcher in an excellent Californian Research Laboratory. He has also the opportunity to report his emotions and those perceived in his meetings in New York on the occasion of the assassination of the President J. F. Kennedy which just coincided with his arrival in USA.